Repentance Education: The Gate of Heaven That is Always Open A Community Outreach Program for The Congregation Of Al-Mukmin Mosque Pekanbaru - Wali Saputra (Aksi Kita: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service initiative aimed to deepen the spiritual understanding and awareness of the Al-Mukmin Mosque congregation in Pekanbaru regarding the Islamic concept of tawbah (repentance). The program was conceived in response to a discernible pattern of moral decline and spiritual disorientation among contemporary Muslim communities, compounded by the underutilization of the mosque as a center for community development and religious formation. Titled "Repentance Education: The Gate of Heaven That Is Always Open," the program offered a structured and transformative response to the congregation's need for meaningful religious enrichment. The implementation followed four sequential phases: preparation, execution, evaluation and reporting, and sustainability assessment. The core educational sessions employed an interactive lecture format integrated with open discussion, question-and-answer exchanges, experiential sharing, and spiritual motivation. Supporting materials — including leaflets and condensed content summaries — were distributed to all participants to reinforce independent learning beyond the sessions. The outcomes exceeded initial expectations on multiple fronts. Participants demonstrated measurable gains in their understanding of the definition, conditions, and virtues of repentance as grounded in the Qur'an and the Hadith. More notably, a significant shift in spiritual consciousness was observed, evidenced by participants' expressed commitment to improving the quality of their worship and drawing closer to Allah. The high level of active engagement throughout the discussion sessions further affirmed the effectiveness of the participatory learning approach employed. The findings confirm that interactive lecture methods, when combined with open dialogue, are effective in facilitating deep internalization of repentance-related values. The sustained support of the mosque leadership, together with a shared commitment to continuing regular religious study, emerged as critical strategic factors in ensuring the program's long-term impact. The initiative also demonstrated the considerable social and spiritual dividends that can be generated through meaningful collaboration between academic institutions and mosque communities. This study concludes that well-designed, participatory repentance education is capable of producing change that is not merely cognitive, but profoundly affective and spiritual. The collaborative model between academic institutions and mosques merits continued development as an effective, sustainable, and contextually responsive framework for nurturing contemporary Muslim communities